(3GdTGaj aj GdLhGH Ydi GdQSGdI GdNGQbI dGHf CHj GdbHGFd YHO GdQMef Hf efUhQs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s ((3TQa GdOjf GdMSf Hf eMeO GdRQjbi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bUQ Yf JCOjI eG jMH dg ef GdMb MeO GdMGeOjf , hdG Edg EdG Gddg EQZGekG dEfha GdLGMOjf s
(3BNQgG (B:s
(3aGdLhGH Gfg JYGdi bO fgi Yf GdXde , hJhYO Ydjg hbGd JYGdi (B: " (3ahjd ddXGdejf ef YPGH TOjO (B" (3Je GdLRA GdKGfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYfhGfGJ HGdMeQI s
(3Ydi MhGTjgG JYdjbGJ hJUMjMGJ hebGHdGJ hHBNQ GdLRA GdChd (B[ (3hQbI (B191 (3C (B] (3SeGY hbQGAI SfI (B1067 (3g` s
(3hgj GdQSGdI GdJi HYK HgG GHf CHj GdbHGFd Edi GdEeGe GdePchQ ai TgQ ThGd hSfI (B608(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis